2022
DOI: 10.1177/02692155221088684
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early rehabilitation on functional exercise tolerance in decompensated heart failure patients: Results of a multicenter randomized controlled trial (ERIC-HF study)

Abstract: Objective To analyze (1) the effect of an aerobic training program on functional exercise tolerance in decompensated heart failure (DHF) patients; (2) to assess the effects of an aerobic training program on functional independence; and (3) dyspnea during activities of daily living. Design A randomized controlled clinical trial with follow-up at discharge. Settings Eight hospitals. Recruitment took place between 9/ 2017 and 3/2019. Group Assignments Patients with DHF who were admitted to the hospital, were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“… 10 The study revealed a significant increase in exercise tolerance and a marked improvement in the left heart function index in the observation group. This evidence underscores the constructive influence of aerobic exercise on cardiovascular rehabilitation in patients, aligning with the findings reported by Delgado et al 11 Another study also revealed significant improvements in physical function indexes and quality of life in the aerobic exercise group at 16 weeks of follow-up. 12 In contrast, Gary et al observed that there were no statistically significant improvements in the results of the 6-minute walking test (6MWT) after a 12-week schedule of aerobic exercise training for patients with HF.…”
Section: Aerobic Exercisesupporting
confidence: 89%
“… 10 The study revealed a significant increase in exercise tolerance and a marked improvement in the left heart function index in the observation group. This evidence underscores the constructive influence of aerobic exercise on cardiovascular rehabilitation in patients, aligning with the findings reported by Delgado et al 11 Another study also revealed significant improvements in physical function indexes and quality of life in the aerobic exercise group at 16 weeks of follow-up. 12 In contrast, Gary et al observed that there were no statistically significant improvements in the results of the 6-minute walking test (6MWT) after a 12-week schedule of aerobic exercise training for patients with HF.…”
Section: Aerobic Exercisesupporting
confidence: 89%